BASIC PRINCIPLES OF THE COGNITIVE COMPONENT OF THE ARTISTIC AND PEDAGOGICAL COMPETENCE OF THE FUTURE TEACHER OF FINE ARTS - O. Smirnova (Academy of Cognitive and Natural Sciences, 2009)
The article reveals the gist of cognitive competence of artistic pedagogical competence of the future art teacher.